Macromol. Rapid Commun. 10/2017. Issue 10 (May 2017) - Song, Yixuan; Meyers, Kevin P.; Gerringer, Joseph; Ramakrishnan, Ramesh K.; Humood, Mohammad; Qin, Shuang; Polycarpou, Andreas A.; Nazarenko, Sergei; Grunlan, Jaime C.
Abstract : Front Cover: A polyelectrolyte‐based nanocoating exhibits super oxygen barrier and humidity‐responsive self‐healing behavior. An 8‐bilayer polyethylenimine/poly(acrylic acid) thin film improves the oxygen barrier of a thick poly(ethylene terephthalate) substrate by more than 1000×. High humidity (symbolized by the thread in this schematic) completely restores the super oxygen barrier of the damaged/cracked coating in just 10 minutes. This fast and high‐efficiency self‐healing is repeatable for at least 10 damaging–healing cycles. Further details can be found in article number1700064 by Y. Song, K. P. Meyers, J. Gerringer, R. K. Ramakrishnan, M. Humood, S. Qin, A. A. Polycarpou, S. Nazarenko* and J. C. Grunlan*.